2013
DOI: 10.5152/akd.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

Increased YKL-40 levels in patients with isolated coronary artery ectasia: an observational study

Abstract: Objective: YKL-40, a new biomarker of localized inflammation, is secreted by macrophages within the atherosclerotic plaques. Coronary artery ectasia (CAE) is a clinical entity with unclear etiopathogenesis. Some studies have revealed that CAE may be a form of atherosclerosis that has more localized and intense inflammatory properties than atherosclerosis. The goal of this study was to investigate YKL-40 and C-reactive protein (CRP) levels in patients with isolated CAE compared to patients with normal coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
10
2
Order By: Relevance
“…Erdogan et al (8) report in the Anatolian Journal of Cardiology that serum YKL-40 levels in patients with isolated CAE and coronary artery disease are significantly higher than that in patients with normal coronary artery (NCA) and this result in those with isolated CAE remains significant even after adjusting for multiple variables. Furthermore, the present study demonstrates, that C-reactive protein (CRR) level in between those with isolated CAE and NCA does not have a significant difference, which is different from the previous study (4).…”
Section: Ykl-40 Kullanimi Koroner Arter Ektazi Için Yeni Bir Beiirteçcontrasting
confidence: 91%
See 1 more Smart Citation
“…Erdogan et al (8) report in the Anatolian Journal of Cardiology that serum YKL-40 levels in patients with isolated CAE and coronary artery disease are significantly higher than that in patients with normal coronary artery (NCA) and this result in those with isolated CAE remains significant even after adjusting for multiple variables. Furthermore, the present study demonstrates, that C-reactive protein (CRR) level in between those with isolated CAE and NCA does not have a significant difference, which is different from the previous study (4).…”
Section: Ykl-40 Kullanimi Koroner Arter Ektazi Için Yeni Bir Beiirteçcontrasting
confidence: 91%
“…Rrevious studies have reported that circulating YKL-40 level is elevated in patients with diabetes and obesity (7)(8)(9)(10). The entire population in the present study has high body mass index, and the prevalence of diabetes in patients with CAE and CAD tends to be higher than in those with NCA, although there is no significant difference between the groups.…”
Section: Ykl-40 Kullanimi Koroner Arter Ektazi Için Yeni Bir Beiirteçmentioning
confidence: 45%
“…Previous studies have reported that circulating YKL-40 level is elevated in patients with diabetes and obesity (7)(8)(9)(10). The entire population in the present study has high body mass index, and the prevalence of diabetes in patients with CAE and CAD tends to be higher than in those with NCA, although there is no significant difference between the groups.…”
contrasting
confidence: 50%
“…Erdoğan et al (8) report in the Anatolian Journal of Cardiology that serum YKL-40 levels in patients with isolated CAE and coronary artery disease are significantly higher than that in patients with normal coronary artery (NCA) and this result in those with isolated CAE remains significant even after adjusting for multiple variables. Furthermore, the present study demonstrates that C-reactive protein (CRP) level in between those with isolated CAE and NCA does not have a significant difference, which is different from the previous study (4).…”
mentioning
confidence: 99%
“…1). Eventually, 11 clinical case-control studies with a total of 1,175 CAD patients and 1,261 healthy subjects met our inclusion criteria for quantitative data analysis (19)(20)(21)(22), (26)(27)(28)(29)(30)(31)(32). The range of publication years of the eligible studies ranged from 2007 to 2013.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%